First record of the tribe Diglottini from South America with description of Diglotta brasiliensis n. sp. (Coleoptera, Staphylinidae, Aleocharinae) - Caron, Edilson; Ribeiro-Costa, Cibele Stramare (Zootaxa, 2008)
The tribe Diglottini Eichelbaum, 1909 comprises two halophilous rove beetle genera Diglotta Champion, 1899, and Paradiglotta Ashe & Ahn, 2004. The tribe contains eight known species distributed in the Nearctic and West-Palaearctic regions, and also Fiji Islands and New Zealand. This tribe is recorded for the first time from South America with the description of a new species, Diglotta brasiliensis n. sp. from southern Brazil (Paraná). Characters of the mouthparts, aedeagus and spermatheca of the new species are illustrated and compared with other Diglotta species. Sexual dimorphism is reported for the first time in the genus.